Pengaruh Persepsi Kualitas Produk dan Persepsi Harga terhadap Minat Beli dengan Kualitas Pelayanan sebagai Moderator - Agnes Ruth Virena; Joseph M.J. Renwarin (UNIVERSITAS KALBIS, 2022)
Coffee consumption in Indonesia is increasing along with the growth of coffee production in Indonesia. Kopi Kenangan is a coffee beverage producer that takes advantage of this opportunity. However, one of its outlets experienced low visitors. Therefore, this study was conducted to determine the effect of consumer perceptions, namely Perception of Product Quality and Price Perception on Purchase Intention as moderated by Service Quality. This study uses quantitative methods and the sample used in this study amounted to 193 respondents using purposive sampling technique with the criteria that they already know the Kenangan Coffee brand and have tried processed coffee drinks. The research data processing used SPSS version 25, and the results showed that Perception of Product Quality and Perception of Price respectively had a significant effect on Purchase Intention, and Service Quality did not play a role as a moderating variable both in the effect of Perception of Product Quality on Purchase Intention, and in the Price Perception of Purchase Intention.